2022
DOI: 10.1177/15593258221115563
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics-Based Approach for Exploring the Immune Cell Infiltration Patterns in Alzheimer’s Disease and Determining the Intervention Mechanism of Liuwei Dihuang Pill

Abstract: Traditional Chinese medicine (TCM) compounds have recently garnered attention for the regulation of immune cell infiltration and the prevention and treatment of Alzheimer’s disease (AD). The Liuwei Dihuang Pill (LDP) has potential in this regard; however, its specific molecular mechanism currently remains unclear. Therefore, we adopted a bioinformatics approach to investigate the infiltration patterns of different types of immune cells in AD and explored the molecular mechanism of LDP intervention, with the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…30 However, the specific molecular mechanisms of its action have not been fully understood. Zhao et al 31 used bioinformatics methods to explore the molecular immune mechanism of Liuwei Dihuang Pill in the treatment of AD by studying the infiltration patterns of different types of immune cells in AD. The study found that in hippocampal tissue samples from AD patients, the infiltration levels of M2 macrophages and quiescent CD4þ memory T cells were higher compared to healthy individuals, and there were significant differences in the infiltration levels of M1 macrophages as well.…”
Section: The Application Of Bioinformatics In the Study Of Chinese He...mentioning
confidence: 99%
“…30 However, the specific molecular mechanisms of its action have not been fully understood. Zhao et al 31 used bioinformatics methods to explore the molecular immune mechanism of Liuwei Dihuang Pill in the treatment of AD by studying the infiltration patterns of different types of immune cells in AD. The study found that in hippocampal tissue samples from AD patients, the infiltration levels of M2 macrophages and quiescent CD4þ memory T cells were higher compared to healthy individuals, and there were significant differences in the infiltration levels of M1 macrophages as well.…”
Section: The Application Of Bioinformatics In the Study Of Chinese He...mentioning
confidence: 99%
“…The pharmacodynamic material basis of the compound cannot be clarified by focusing only on the components of traditional Chinese medicine contained in the compound or the ingredients with pharmacological activity in vitro. Therefore, there are serious methodological defects in the material basis research of LWDHP based on TCM database (such as TCM systematic pharmacology database and analysis platform TCMSP), which usually results in highly homogeneous research results [22][23][24].The pharmacochemistry of TCM serum is an effective method to study the pharmacochemistry and compatibility of the compound. The prototype components of LWDHP in serum and cerebrospinal fluid of SD rats were detected after intragastric administration of 3 mL LWDHP solution (6.75 g/kg).…”
Section: Materials Basis Of Lwdhpmentioning
confidence: 99%